Analysis of Teachers' Teaching Skills in Improving Student Motivation - Sabrina, Rifdah; Sarianto, Debi; Andika, Reno; Ardianto, Firdaus (Al-kayyis: Journal of Islamic Education, 2025)
Student interest in learning Islamic Cultural History is relatively low, with only around 33.3% of students expressing interest in learning Islamic Cultural History. This situation poses a challenge for Islamic Cultural History teachers in increasing student enthusiasm and motivation in learning Islamic Cultural History. This study aims to analyze the teaching skills of Islamic Cultural History teachers in enhancing students' learning motivation, as well as to examine how Islamic Cultural History teachers plan their lessons to improve students' learning motivation. This study employs a descriptive qualitative method. Data sources were obtained from fifteen informants through in-depth interviews selected using purposive sampling techniques. All informants were active students, Islamic Cultural History teachers, school principals, and curriculum vice principals. All interview results were then analyzed thematically using the Miles and Huberman technique. the analysis results indicate that Islamic Cultural History teachers possess good teaching skills in enhancing students' learning motivation, as evidenced by their knowledge and continuous study of teaching skills. This is further supported by interviews with school principals regarding the quality of Islamic Cultural History teachers and the excellent learning outcomes of students in Islamic Cultural History. Additionally, the lesson planning is quite good because Islamic Cultural History teachers have developed teaching materials as part of their lesson planning before teaching. This study can serve as an initial reference for future researchers in examining this issue within different contexts and contexts